THE EFFECT OF ATTITUDE TOWARDS E-TAX SYSTEMS, ADOPTION OF E-TAX SYSTEMS, ISOMORPHIC FORCES, AND TRUST IN TAX AUTHORITY TO TAX COMPLIANCE (CASE STUDY ON SMES LISTED IN KPP PRATAMA MEDAN PETISAH) - Patricia Octavia Manalu; Widyahayu Warmmeswara Kusumastati; Muhamad Safiq (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to investigate whether attitude towards e-tax systems, trust in tax authority, and adoption of e-tax systems could influence voluntary tax compliance and whether adoption of e-tax systems and the isomorphic forces could increase enforced tax compliance. The sample was taken from 152 SMEs taxpayer registered in KPP Pratama Medan Petisah and processed using IBM SPSS Statistics 25, then it was analyzed by using multiple regression tests. The findings showed that attitude towards electronic tax system, trust in the tax authority, and adoption of electronic tax systems have a positive significant influence on voluntary tax compliance. The adoption of e-tax systems and isomorphic forces also has a positive significant influence on enforced tax compliance.